Hubungan Supervisi Akademik Pengawas Pendidikan Agama Kristen dengan Kinerja Guru - Amran Maher Dionizius Isu (SIKIP: Jurnal Pendidikan Agama Kristen, 2021)
The purpose of this study was to determine and explain the relationship between academic supervision of Christian religious education supervisors on the performance of Christian religious education teachers in the Ministry of Religion of South-Central Timor Regency. this type of quantitative research is used for data collection, data analysis, and interpretation of analysis results to obtain information for drawing conclusions and making decisions. So, the results obtained at the time of the study were: first, The influence of supervisory planning activities on the work performance of Christian religious education teachers includes supervisory planning activities or tasks (X1) significantly affects the performance of Christian religious education teachers (Y); second, The effect of the implementation of supervisory duties on the work performance of Christian religious education teachers includes Supervisory Supervision Activities or tasks (X2) significantly affects the performance of Christian religious education teachers (Y). This means that the supervisor's follow-up activity (X3) has a significant effect on the performance of Christian religious education teachers (Y). AbstrakTujuan yang dicapai pada penelitian ini adalah untuk mengetahui dan menjelaskan hubungan supervisi akademik pengawas pendidikan agama kristen terhadap kinerja guru pendidikan agama kristen di wilayah kementerian agama Kabupaten Timor Tengah Selatan. jenis penelitian kuantitatif, digunakan untuk pengumpulan data, analisis data, dan interpretasi hasil analisis untuk mendapatkan informasi guna penarikan kesimpulan dan pengambilan keputusan. Maka hasil yang diperoleh pada saat penelitian adalah: Pertama, pengaruh kegiatan perencanaan pengawas terhadap kinerja kerja guru pendidikan agama Kristen meliputi kegiatan atau tugas perencanaan Pengawas (X1) berpe-ngaruh secara signifikan terhadap kinerja guru Pendidikan agama Kristen (Y); kedua, pengaruh pelaksanaan tugas supervisi pengawas terhadap kinerja kerja guru pendidikan agama Kristen meliputi kegiatan atau tugas supervise pengawas (X2) berpengaruh secara signifikan terhadap kinerja guru Pendi-dikan agama Kristen (Y). Hal ini berarti bahwa kegiatan tindaklanjut pengawas (X3) berpengaruh secara signifikan terhadap kinerja guru pendidikan agama kristen (Y).